Education, unemployment and migration - Wolfgang Eggert; Tim Krieger; Volker Meier (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2009)
This paper studies a two-region model in which unemployment, education decisions andinterregional migration are endogenous. The poorer region exhibits both lower wagesand higher unemployment rates, and migrants to the richer region are disproportionallyskilled. The brain drain from the poor to the rich region is accompanied by strongerincentives to acquire skills even for immobile workers. Regional shocks tend to affectboth regions in a symmetric fashion, and skilled-biased technological change reduceswages of the unskilled. Both education and migration decisions are distorted by auniform unemployment compensation, which justifies a corrective subsidization.
Keywords: H23; I20; J61; J64; R10; 330; Brain drain; brain gain; education; unemployment; interregional migration; externalities